Plurihormonal Pit-1 lineage adenoma presenting as meningitis with recurrence after somatostatin analogue. (21st March 2019) - Olmedilla, Yoko; Khan, Shoaib; Young, Victoria; Joseph, Robin; Cudlip, Simon; Ansgorge, Olaf; Grossman, Ashley; Pal, Aparna
Summary: A 21 year-old woman was found to have a pituitary macroadenoma following an episode of haemophilus meningitis. Biochemical TSH and GH excess was noted, although with no clear clinical correlates. She was treated with a somatostatin analogue (SSA), which restored the euthyroid state and controlled GH hypersecretion, but she re-presented with a further episode of cerebrospinal fluid (CSF) leak and recurrent meningitis. Histology following transsphenoidal adenomectomy revealed a Pit-1 lineage plurihormonal adenoma expressing GH, TSH and PRL. Such plurihormonal pituitary tumours are uncommon and even more unusual to present with spontaneous bacterial meningitis. The second episode of CSF leak and meningitis appears to have been due to SSA therapy-induced tumour shrinkage, which is not a well-described phenomenon in the literature for this type of tumour. Learning points: Pit-1 lineage GH/TSH/PRL-expressing plurihormonal pituitary adenomas are uncommon. Moreover, this case is unique as the patient first presented with bacterial meningitis. Inmunohistochemical plurihormonality of pituitary adenomas does not necessarily correlate with biochemical and clinical features of hormonal hypersecretion. Given that plurihormonal Pit-1 lineage adenomas may behave more aggressively than classical pituitary adenomas, accurate pathological characterization of these tumours has an increasing prognostic relevance. Although unusual, a CSF leak and meningitis may be precipitated by SSA therapy of a pituitary macroadenoma via tumour shrinkage.